2019
DOI: 10.1016/j.pmrj.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Vertebral Endplate Fractures: A Retrospective Study on a Rare Etiology of Back Pain in Youth and Young Adults

Abstract: Background: Posterior lumbar vertebral endplate fracture occurs with avulsion of the ring apophysis from the posterior vertebral body. Although this has been described in adolescents and young adults, proper diagnosis is often delayed or missed entirely. Surgery may be curative. Objective: To determine the common clinical features and treatment outcomes in youth and young adults with posterior lumbar vertebral endplate fractures. Design: Retrospective case series. Setting: Academic medical institution. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The typical pathological feature of ring apophysis fracture inducing the displacement of the posterior edge of the vertebral body or the fracture entering into the spinal canal makes nerve root decompression insufficient. 5 Therefore, it is more meaningful to compare PELD efficacy in treating APRAF accompanied with LDH and LDH alone. It is reported that PELD achieved satisfactory results in treating PRAF (type III) accompanied by LDH, with an excellent and good rate of 93.4%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The typical pathological feature of ring apophysis fracture inducing the displacement of the posterior edge of the vertebral body or the fracture entering into the spinal canal makes nerve root decompression insufficient. 5 Therefore, it is more meaningful to compare PELD efficacy in treating APRAF accompanied with LDH and LDH alone. It is reported that PELD achieved satisfactory results in treating PRAF (type III) accompanied by LDH, with an excellent and good rate of 93.4%.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 4 , 6 Owing to the very low incidence rate of PRAF, clinicians often lack awareness of this condition, leading to a delayed or missed diagnosis. 5 PRAF can be accurately diagnosed using computed tomography (CT) evaluation. 5 Based on the CT scan fracture positioning, Takata et al classified PRAF into four categories.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…JDH was defined as LDH on MRI with concordant radicular leg pain or radiculopathy, regardless of the presence or absence of back pain, in patients 20 years old or younger when the clinical diagnosis was first established 14 . The age of 20 years was used because the growth of the skeletal system is nearly completed at the end of the second decade of life 15 . For each participant in this study, the study protocol was briefly explained and written/electronic consent was obtained.…”
Section: Methodsmentioning
confidence: 99%